A new teaching model with artificial teeth containing simulated pulpal tissue - Hamid Razavian; Kimia Hanjani (Wolters Kluwer Medknow Publications, 2021)
Background: This study aimed to evaluate the use of artificial teeth for endodontic training for dental students. Materials and Methods: The following aspects of the artificial teeth were approved by the endodontists in Isfahan University of Medical Science: internal and external anatomy; coronal pulp chambers regarding their size, shape, and canal path; the root canals regarding their size, shape, and position; filling the pulp chamber and root canals by considering the texture, quantity, color, and ease of handling; and resin hardness and visualization of the radiographic image. Results: The results showed favorable opinions regarding the internal and external anatomy, coronal pulp chamber, root canal (s), handling, and radiographic imaging. The contents of the pulp space and hardness of the teeth were satisfactory. Conclusion: The artificial teeth tested have the potential to replace the natural teeth in preclinical training.